KARAKTERISTIK ION Na+ dan Ca2+ TELAGA COASTAL AQUIFER DAERAH KAPUR MALANG SELATAN PADA PERIODE PASANG-SURUT - Barroroh Barroroh (El-QUDWAH, 2007)
Ion Ca2+ discharge have been investigated due to soil structrure around coastal aquifer lake in limestone area at Bajulmati district Malang. As well as dynamica of ion Na+ consentration according tidal elevation dynamic on the lake. Consentration of Na+ and Ca2+ have been measured quantitatively including phisyco-chemistry variable influencing them, i.e. pH and tempeture. This study carried out in two step, i.e. the fisrt, ion Ca2+ consentration measure horisontally dan vertically for mapping of the origin of ion Ca2+ discharge. The second is measurement of ion Na+ consentration at definite sampling location for five different time with an hour range of each between tidal sea cycle. The result is compared with sea elevation measurement as long as tidal sea cycle and measurement of distance between coastal and the lake give a discription about sea water intrusion dinamic to the lake. On mapping of ion Ca2+ consentration horisontally and vertically, show that the discharge map of ion Ca2+ originate only from a location in the edge of the lake that have cross section position to the dam. It seem that the water in lake is originate from a groundwater river. The ion Na+ consentration dynamic show a linear pattern according with tidal sea elevation dynamic. There is a delay as long as intrussion process, while the dynamical curve of ion Na+ consentration have a symmettrical graphic to tidal sea elevasion dynamic curve.Keyword: mapping, dynamic, Ca2+, Na+, coastal aquifer lake, limestone area